2018
DOI: 10.1111/acel.12859
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and telomerase activity in T cells are biomarkers of high‐performing centenarians

Abstract: It is generally recognized that the function of the immune system declines with increased age and one of the major immune changes is impaired T‐cell responses upon antigen presentation/stimulation. Some “high‐performing” centenarians (100+ years old) are remarkably successful in escaping, or largely postponing, major age‐related diseases. However, the majority of centenarians (“low‐performing”) have experienced these pathologies and are forced to reside in long‐term nursing facilities. Previous studies have po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 42 publications
2
57
0
Order By: Relevance
“…Senescent cells secrete a variety of inflammatory cytokines, known as the senescence‐associated secretory phenotype (SASP), triggered by persistent DNA damage (Rodier et al, ; Tedone et al, ). Vascular inflammation, calcification, and the progression of atherosclerosis are also associated with SASP (Csoka et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Senescent cells secrete a variety of inflammatory cytokines, known as the senescence‐associated secretory phenotype (SASP), triggered by persistent DNA damage (Rodier et al, ; Tedone et al, ). Vascular inflammation, calcification, and the progression of atherosclerosis are also associated with SASP (Csoka et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…mtDNA levels during T cell stimulation decrease with age, but healthy centenarians escape this decline Previously, we identified genes and pathways potentially involved in the process of healthy human immune cell aging and longevity through the study of stimulated PBMCs from a well-characterized population of 114 individuals aged 23-113 yr (Tedone et al 2019). PBMCs are a heterogeneous cell population mainly consisting of T cells, a major component of human immune responses.…”
Section: Ddmdm For Quantitation Of Mtdna Copy Number In Single Cellsmentioning
confidence: 99%
“…Interestingly, healthy centenarians appeared to retain more mtDNA molecules and less major mtDNA deletions, suggesting mtDNA copy number and maintenance during immune cell stimulation is a potential biomarker of healthy aging. In addition, previous studies have shown mtDNA to be a critical player in the NLRP3 inflammation pathway (Zhou et al 2011;Zhong et al 2018) and we recently reported involvement of the NLRP3 inflammasome in centenarian longevity and healthy aging (Tedone et al 2019). Additional studies are required to better understand the contribution that mtDNA plays in chronic inflammation and aging, not only for its role in metabolism but also as a signaling molecule.…”
Section: Discussionmentioning
confidence: 92%
“…Previously, we identified genes and pathways potentially involved in the process of healthy human aging and longevity through the study of stimulated peripheral blood mononuclear cells In contrast, upon antigen-specific activation T cells rapidly divide and exhibit dramatic changes in gene expression (Zhao et al 2014;Tedone et al 2019) and metabolic features (Dimeloe et al 2017). Activated T cells initiate immune responses such as discriminating between healthy and abnormal (e.g.…”
Section: Mtdna Levels During T Cell Stimulation Decrease With Age Butmentioning
confidence: 99%
See 1 more Smart Citation